Co-expressing fast channelrhodopsin with step-function opsin overcomes spike failure due to photocurrent desensitization in optogenetics: a theoretical study. (1st April 2022) - Bansal, Himanshu; Pyari, Gur; Roy, Sukhdev
Abstract: Objective. A fundamental challenge in optogenetics is to elicit long-term high-fidelity neuronal spiking with negligible heating. Fast channelrhodopsins (ChRs) require higher irradiances and cause spike failure due to photocurrent desensitization under sustained illumination, whereas, more light-sensitive step-function opsins (SFOs) exhibit prolonged depolarization with insufficient photocurrent and fast response for high-fidelity spiking. Approach. We present a novel method to overcome this fundamental limitation by co-expressing fast ChRs with SFOs. A detailed theoretical analysis of ChETA co-expressed with different SFOs, namely ChR2(C128A), ChR2(C128S), stabilized step-function opsin (SSFO) and step-function opsin with ultra-high light sensitivity (SOUL), expressing hippocampal neurons has been carried out by formulating their accurate theoretical models. Main results. ChETA-SFO-expressing hippocampal neurons shows more stable photocurrent that overcomes spike failure. Spiking fidelity in these neurons can be sustained even at lower irradiances of subsequent pulses (77% of initial pulse intensity in ChETA-ChR2(C128A)-expressing neurons) or by using red-shifted light pulses at appropriate intervals. High-fidelity spiking upto 60 Hz can be evoked in ChETA-ChR2(C128S), ChETA-SSFO and ChETA-SOUL-expressing neurons, which cannot be attained with only SFOs. Significance. The present study provides important insights about photostimulation protocols for bi-stable switching of neurons. This new approach provides a means for sustained low-power, high-frequency and high-fidelity optogenetic switching of neurons, necessary to study various neural functions and neurodegenerative disorders, and enhance the utility of optogenetics for biomedical applications.